A STUDY ON BACTERIOLOGICAL PROFILE AND ANTIBIOTIC SUSCEPTIBILITY PATTERN OF SURGICAL SITE INFECTIONS IN A TERTIARY CARE HOSPITAL - USHARANI, PURIMITLA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The present study was aimed to evaluate the prevalence, microbiological profile, and antibiograms of pathogenic microorganisms causing surgical site infections. Methods: The present study was conducted in the Department of Microbiology, Dr. Patnam Mahender Reddy Institute of Medical Sciences, Telangana. The study was conducted from the period of April 2020 to April 2021. Three hundred pus samples were analyzed for culture isolation and identification using standard protocols. Antibiotic susceptibility pattern of each isolate was performed by standard disc diffusion method by following The Clinical and Laboratory Standard Institute guidelines. Results: A total of monomicrobial isolates 165 (55%) and polymicrobial isolates 13 (4.4%) were obtained from 300 pus samples and remaining 122 (40.6%) pus samples were sterile. The predominant bacteria were Staphylococcus aureus 50 (30.3%) followed by Pseudomonas aeruginosa 39 (23.6%) in monomicrobial infection and Klebsiella oxytoca + P. aeruginosa 3 (23%) in polymicrobial infection. The results of antibiogram of S. aureus which showed the highest sensitivity to antibiotics like linezolid 47 (94%) and doxycycline 42 (80%) compared to other antibiotics used for antibiotic susceptibility testing. Among the Gram-negative bacteria, the prevalent organism was Klebsiella species which showed the highest sensitivity to antibiotic meropenem 32 (86.5%). Conclusion: The predominant bacterium isolated was S. aureus followed by P. aeruginosa in monomicrobial infection and K. oxytoca + P. aeruginosa in polymicrobial infection. Controlling the morbidity of surgical site infections is aided by meticulous surgical procedures, careful sterilization, judicious use of antibiotics, improved operating theater and ward conditions, control of malnutrition and obesity, management of infective foci, and diseases such as diabetes.